The Interest Rate Channel in Turkey: An Investigation with Kalman Filter Approach - Sarac, Taha Bahadır; Ucan, Okyay (International Journal of Economics and Financial Issues, 2013)
The monetary authority affects the aggregate demand and investment expenditure via controlling short run interest rates. It is important to satisfy the price stability together with working interest rate channel. This study aims to investigate the validity of interest rate channel in Turkey since the inflation targeting period starting with the year 2002. The sample period covers quarterly data from 1990:1 to 2011:3. It is stated that after the 2002 efficiency of interest rate channel increases. Keywords: Kalman Filter; Markov Switching; Monetary Policy; Turkey JEL Classifications: C32; C34; E52